Resonance assignment of PsbP: an extrinsic protein from photosystem II of Spinacia oleracea - Rathner, Adriana; Chandra, Kousik; Rathner, Petr; Horničáková, Michaela; Schlagnitweit, Judith; Kohoutová, Jaroslava; Ettrich, Rüdiger; Müller, Norbert (Biomolecular NMR assignments, 2015)
PsbP (23 kDa) is an extrinsic eukaryotic protein of photosystem II found in the thylakoid membrane of higher plants and green algae. It has been proven to be indispensable for proper functioning of the oxygen evolving complex. By interaction with other extrinsic proteins (PsbQ, PsbO and PsbR), it modulates the concentration of two cofactors of the water splitting reaction, Ca(2+) and Cl(-). The crystallographic structure of PsbP from Spinacia oleracea lacks the N-terminal part as well as two inner regions which were modelled as loops. Those unresolved parts are believed to be functionally crucial for the binding of PsbP to the thylakoid membrane. In this NMR study we report (1)H, (15)N and (13)C resonance assignments of the backbone and side chain atoms of the PsbP protein. Based on these data, an estimate of the secondary structure has been made. The structural motifs found fit the resolved parts of the crystallographic structure very well. In addition, the complete assignment set provides preliminary insight into the dynamic regions.
Keywords: Proton Magnetic Resonance Spectroscopy; Photosystem II Protein Complex; sekvence aminokyselin; PsbP; Photosystem II; rostlinné proteiny; Spinacia oleracea; Intrinsic disorder; Plant Proteins; Oxygen evolving complex; sekundární struktura proteinů; krystalografie rentgenová; Dynamic regions; Protein Structure, Secondary; fotosystém II (proteinový komplex); molekulární sekvence - údaje; Crystallography, X-Ray; protonová magnetická rezonanční spektroskopie; Molecular Sequence Data; Amino Acid Sequence